Legal aspects of the activities of the specialized classes in the sport youth sports schools - Андріанова, О. А. (Slobozhanskyi Herald of Science and Sport, 2011)
Disclosed here is the legal aspect of the specialized classes in the sport. It is considered legal documents regulating the activities of the youth sports schools and specialized classes in the sports and secondary schools as well as agreements on cooperation of secondary schools and the youth sports schools. The challenges of a legal provision of specialized classes in the sport. Are revealed to develop new regulations, more regulatory activities of the specialized classes for sport.